Strategi Meningkatkan Motivasi Kerja Dalam Mendorong Kinerja Karyawan di The Organizer Jimbaran, Bali - Pratiwi, Intan Pradnya; Paramita, Ratri; Arjaya, Ketut (Journal of Event and Convention Management, 2025)
This study aims to analyze the strategies to increase work motivation and improve employee performance at The Organizer, a company engaged in the event industry located in Jimbaran, Bali. Motivation is an important psychological factor that drives individuals to work optimally. By employing a qualitative descriptive approach, data were collected through participatory observation, in-depth interviews, and documentation study. The informants in this study include the owner, inhouse employees, and semi- inhouse employees selected through purposive sampling. The research findings reveal gaps in motivation management, such as inconsistent incentive systems, ineffective internal communication, and lack of recognition and appreciation. Based on ISO 9001:2015 standards, several strategies are proposed, including strengthening leadership, developing competencies, improving communication, and enhancing work environments. These strategies are expected to increase employee motivation and performance sustainably. The findings of this study are expected to contribute to the development of human resource management practices, especially in the event industry, where employee motivation plays a critical role in delivering excellent service to clients and ensuring event success. Future research can explore the quantitative impact of these strategies on organizational performance.